the answer is -35/66
to divide fractions you take the reciprocal of the second fraction (switching the numerator and denominator) and multiply it so the equation turns into
5/6*(-7/11) = -35/66
hope you understand now
Hello!
Ok so we have y= 7/3x + 5 and initial condition of x=-3 so we just plug -3 in for x and chug along at this point! :)
y=(7/3)*(-3/1)+5= -7+5 = -2
Hope this helps! Any questions please just ask! Thank you!!
Answer:
0.3 kg : 5 kg
Step-by-step explanation:
just simplified
BRAINLIEST PLS!